The role of pelvic rehabilitation in quality of life in a patient harboring metastatic chordoma: a case report - Dalila Gonçalves Duarte; Matheus Fernandes de Oliveira; Eduardo de Arnaldo Silva Vellutini; Ricardo Caponero; Katia Cristina Camondá Braz (Brazilian Journal of Oncology)
Introduction: Chordoma is a malignant tumor that usually involves the axial skeleton. Intradural chordomas are even rarer and 37 cases have been reported to the best of our knowledge. We present a case of a patient with an atypical metastatic diffuse intradural spinal involvement.